2013
DOI: 10.1136/bcr-2012-008161
|View full text |Cite
|
Sign up to set email alerts
|

Combined infection of vertebroplasty and aortic graft after intravesical BCG treatment

Abstract: We report a 58-year-old man with spondylodiscitis by Mycobacterium bovis-BCG 3 years after intravesical BCG treatment, and shortly after a vertebroplasty. Further examination showed a psoas abscess and oedema around an endovascular aortic graft, which had been placed 1 year earlier. Puncture of the psoas abscess also grew M bovis-BCG. The patient recovered with a combination of antituberculous treatment and surgery. With hindsight a mycotic aneurysm had been present at the time of aortic graft placement and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
1
25
0
2
Order By: Relevance
“…Other reasons that suggest a possible imminent increase is the emergence of infections by atypical mycobacteria and intravesical BCG injections for bladder cancer. Mycotic aneurysm of the aorta arising from M. intracellulare has been already reported [34], while in a recent review of the literature 2 of the 28 cases were due to BCG [8], [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reasons that suggest a possible imminent increase is the emergence of infections by atypical mycobacteria and intravesical BCG injections for bladder cancer. Mycotic aneurysm of the aorta arising from M. intracellulare has been already reported [34], while in a recent review of the literature 2 of the 28 cases were due to BCG [8], [12].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the English literature from 2008 to today revealed 28 more cases (Table 1) [3], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], specifically 18 men and 10 women with a mean age of 44.64 ± 18.16 years (range 16–84). 7 patients had a history of pulmonary tuberculosis and had previously received anti-tuberculosis medication.…”
Section: Discussionmentioning
confidence: 99%
“…Intravesical BCG therapy for the treatment of superficial bladder cancer has a low risk of extravesical complications, which are rare (5), but adverse effects such as cystitis, a fever, hematuria, prostatitis, arthralgias, and reactive arthritis are relatively common. The first study to mention tuberculous spondylitis caused by intravesical BCG therapy was reported in 1992, but only 13 cases related to intravesical BCG therapy for bladder cancer have been reported since (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) (Table). In most cases, BCG spondylitis develops several months after intravesical BCG therapy, while some cases may develop several years later, but the cause is unknown (13).…”
Section: Discussionmentioning
confidence: 99%
“…The first study to mention tuberculous spondylitis caused by intravesical BCG therapy was reported in 1992, but only 13 cases related to intravesical BCG therapy for bladder cancer have been reported since (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) (Table). In most cases, BCG spondylitis develops several months after intravesical BCG therapy, while some cases may develop several years later, but the cause is unknown (13). It is important to confirm the history of intravesical BCG for the differential diagnosis because M. bovis BCG may spread hematogenously to distant sites over the course of months or years and develop into M. bovis BCG infection.…”
Section: Discussionmentioning
confidence: 99%
“…A very rare, and sometimes fatal, consequence of systemic BCG infection (BCG-osis) is the formation of peripheral and aortic aneurysms. Only four reported cases have undergone endovascular repair, 2 thoracic endovascular aneurysm repairs (TEVARs) for distal descending thoracic aneuryms and 2 endovascular aortic aneurysm repairs (EVARs) for infrarenal aneurysms 4–7. We describe the first reported endovascular repair of an incidentally found proximal descending aortic aneurysm 15 months following systemic BCG-osis secondary to intravesical BCG therapy.…”
Section: Introductionmentioning
confidence: 99%